Guided waves in a stiffened composite laminate with a delamination. (May 2016) - Ricci, Fabrizio; Monaco, Ernesto; Maio, Leandro; Boffa, Natalino D; Mal, Ajit K
The integrity of safety-critical structural composites can be enhanced by the use of innovative ultrasonic nondestructive evaluation techniques. Among the various existing techniques, guided wave methods provide a good promise in terms of sensitivity to a variety of damage types or defects and the extent of the area that can be monitored, given the ability of these waves to travel relatively long distances within the structure under investigation. In comparison with isotropic metallic structures, wave propagation in composite structures presents additional complexity for effective damage identification. The material inhomogeneity, anisotropy, and the multilayered construction of composite materials lead to significant dependence of wave modes on laminate layup configurations, direction of propagation, frequency, and interface conditions. In this article, a specific structure will be analyzed with different levels of complexities in an effort to determine the propagation characteristics of the waves. The investigated structure is a stiffened composite plate of finite thickness and infinite lateral dimensions. The work is carried out using theoretical analysis, numerical modeling, and laboratory experiments. Numerical (finite element) simulations are used for more realistic models, where the geometric and material complexities present practical difficulties in direct analysis using theoretical constructs only.